The Relationship Between Animal Protein Consumption Patterns and the Incidence of Anemia in Adolescent Girls at MTS Darul Hidayah Sriminosari, East Lampung - Dera Elva Junita; Betty Leli Kristiana; Desti Ambar Wati; Amali Rica Pratiwi; Andi Mulyono (Indonesian Journal of Health Research and Development, 2024)
MTs Darul Hidayah is one of 7 schools whose teenage girls experience anemia at the highest rate of 70% in the Labuhan Maringgai Community Health Center Nutrition Program. The condition of iron nutritional anemia is caused by several interrelated factors, including the insufficient amount of iron in food due to low consumption of animal protein sources. Therefore, research was conducted which aimed to analyze the relationship between animal protein consumption patterns and the incidence of anemia in young women at MTs Darul Hidayah. The type of research is quantitative with an analytical survey method using a cross sectional design approach. The research was carried out in December 2022 at MTs Darul Hidayah. Sampling was carried out by purposive sampling. The population in this study were all 101 young women at MTs Darul Hidayah classes VII, VIII and IX. The total sample after screening was 69 young women who had anemia, where each class had a sample to represent and meet the inclusion criteria. Data on animal consumption patterns was obtained using the FFQ (Food Frequency Questionnaire) Form. Hemoglobin levels were measured using a Family Dr. The statistical test used for analysis is the Fisher Exact Test. The research results show that 69.6% of young women never consume animal protein, 53.6% have chronic energy deficiency and 55.1% have moderate anemia. The results of the statistical test analysis show that there is a relationship between animal protein consumption patterns and the incidence of anemia in young women at MTs Darul Hidayah Sriminosari East Lampung with a p-value = 0.007 (p-value <0.05). So, it is concluded that there is a relationship between animal protein consumption patterns and the incidence of anemia in young women at MTs Darul Hidayah.